Leveraging Telehealth to improve access to care: a qualitative evaluation of Veterans' experience with the VA TeleSleep program - Francesca M. Nicosia; Bhavika Kaul; Annette M. Totten; Molly C. Silvestrini; Katherine Williams; Mary A. Whooley; Kathleen F. Sarmiento (BMC, 2021)
Abstract Background Obstructive sleep apnea is common among rural Veterans, however, access to diagnostic sleep testing, sleep specialists, and treatment devices is limited. To improve access to sleep care, the Veterans Health Administration (VA) implemented a national sleep telemedicine program. The TeleSleep program components included: 1) virtual clinical encounters; 2) home sleep apnea testing; and 3) web application for Veterans and providers to remotely monitor symptoms, sleep quality and use of positive airway pressure (PAP) therapy. This study aimed to identify factors impacting Veteran's participation, satisfaction and experience with the TeleSleep program as part of a quality improvement initiative. Methods Semi-structured interview questions elicited patient perspectives and preferences regarding accessing and engaging with TeleSleep care. Rapid qualitative and matrix analysis methods for health services research were used to organize and describe the qualitative data. Results Thirty Veterans with obstructive sleep apnea (OSA) recruited from 6 VA telehealth "hubs" participated in interviews. Veterans reported positive experiences with sleep telemedicine, including improvements in sleep quality, other health conditions, and quality of life. Access to care improved as a result of decreased travel burden and ability of both clinicians and Veterans to remotely monitor and track personal sleep data. Overall experiences with telehealth technology were positive. Veterans indicated a strong preference for VA over non-VA community-based sleep care. Patient recommendations for change included improving scheduling, continuity and timeliness of communication, and the equipment refill process. Conclusions The VA TeleSleep program improved patient experiences across multiple aspects of care including a reduction in travel burden, increased access to clinicians and remote monitoring, and patient-reported health and quality of life outcomes, though some communication and continuity challenges remain. Implementing telehealth services may also improve the experiences of patients served by other subspecialties or healthcare systems.